The Role of Opportunity Recognition in Mediating the Effects of Self-Efficacy and Teacher Support on Junior High School Students’ Entrepreneurial Intentions - Annisa Dildha Surya; Armiati Armiati; M Topit Hidayat (Jurnal Pemberdayaan Masyarakat, 2026)
This study aims to examine the mediating role of opportunity recognition in the effects of self-efficacy and teacher support on students’ entrepreneurial intentions at SMP Negeri 2 Malalak. This study uses a quantitative design, and data collection is conducted through a questionnaire administered to students selected as the research sample. The analysis was conducted using SEM-PLS (Structural Equation Modeling-Partial Least Squares) to test the proposed relationships between variables. The results show that self-efficacy and teacher support have a significant effect on opportunity recognition. In addition, self-efficacy directly affects students’ entrepreneurial intentions, whereas teacher support does not. However, opportunity recognition significantly influences entrepreneurial intention and serves as an important mediating variable, strengthening the effects of both self-efficacy and teacher support on entrepreneurial intention. These results underline the crucial role of opportunity recognition in fostering entrepreneurial intentions among students. Theoretically, this study supports the relevance of Social Cognitive Theory and the Theory of Planned Behavior in explaining the development of entrepreneurial intention, particularly within the context of entrepreneurship education at the junior secondary school level.